Food relocation and the nesting behavior in Scarabaeus and Kheper (Coleoptera: Scarabaeinae) - Halffter, Gonzalo; Halffter, Violeta; Favila, Mario E. (Instituto de Ecología, A.C., 2011)
In recent years much has been learned about the intrasexual relationships and nesting behavior of Scarabaeus Linnaeus and Kheper Janseen. In this study, based on the published literature, aswell as our unpublished observations, the intra- and intersexual relationships during periods of feeding, copulation and nesting are analyzed in detail for both genera. We define two types of behavior: 1) One that we refer to as the sacer type, the most characteristic traits of which are the male offering the female a prenuptial ball of dung which she consumes but does not use for nesting; later when the ovary is mature the female can nest alone without copulating again and without the support of the male. 2) That which occurs in several African species of Scarabaeus and Kheper where the female copulates with different males, but once the ovary is developed nesting is a joint activity carried out by the male and female; the female making one or several brood balls from the rolled and buried dung ball and all of the brood balls receiving postoviposition care. Although almost all nesting females store sperm from previous copulations in their spermathecae, the presence of the last male mate during nesting appears to be associated with an increase in his paternity as he is the last male to have copulated with the female and prevents the intrusion of other males.